Virtues and vices - Muñoz Sánchez, Olmer Alveiro; Flórez R., Jorge Alejandro (Discusiones Filosóficas, 2009)
This paper is a translation of the work Virtues and vices, attributed with some doubt to Aristotle, due to its resemblance with several fragments from On the passions by the Roman editor of Aristotle’s Works, Andronicus of Rhodas. Virtues and vices should be interesting by itself. It contains an enumeration of the virtues and vices that correspond to each of the three parts of the soul, according to Plato’s division. The richness of this work comes from the fact that, in this enumeration, for each virtue or vice we are given its cause, circumstances and results, together with the other virtues and vices that accompany them.